A small-molecule chemosensor for the selective detection of 2, 4, 6-trinitrophenol (TNP). Issue 1 (28th November 2014) - Pan, Jianting; Tang, Fang; Ding, Aixiang; Kong, Lin; Yang, Longmei; Tao, Xutang; Tian, Yupeng; Yang, Jiaxiang
Abstract : A pyridine-based receptor (L ) was synthesised and characterized, which can serve as a small-molecule sensor for the specific recognition of TNP. Abstract : A pyridine-based small-molecule receptor (L ) for the specific recognition of TNP was synthesised and characterised by 1 H NMR, 13 C NMR and FT-IR spectra, and the optical properties were studied by UV-Vis absorption and PL spectra. The results showed that the fluorescence ofL was strongly quenched by picric acid accompanied by an obvious colour change from transparent to yellow, which indicated that the receptorL can serve as a small-molecule sensor for TNP. Crystal structure determination and theoretical calculation of the corresponding host–guest complexL·TNP were also performed.